Molecular Mechanisms and Functions of lncRNAs in the Inflammatory Reaction of Diabetes Mellitus. (19th October 2021) - Huang, Linjuan; Hu, Xiaolei
Abstract : Diabetes is a chronic inflammatory state, and several studies have shown that the mechanisms of insulin resistance and abnormal islet β -cell function in diabetes are closely related to inflammatory reactions. Inflammation plays a critical role in diabetic complications. Long noncoding RNAs (lncRNAs), a new area of genomic research for gene regulation, have complex biological functions in various aspects of cellular biological activity. Recent studies have shown that lncRNAs are associated with the regulation of inflammatory responses in various ways, including at the epigenetic, transcriptional, and posttranscriptional levels. This paper presents a brief review of studies on the mechanisms of lncRNAs in diabetic inflammation. The purpose of this article is to determine the role of lncRNAs in the process of diabetic inflammation and to provide new strategies for the use of lncRNAs in the treatments for diabetic inflammation.